2021
DOI: 10.1002/aenm.202103328
|View full text |Cite
|
Sign up to set email alerts
|

Determining Structure‐Activity Relationships in Oxide Derived CuSn Catalysts During CO2 Electroreduction Using X‐Ray Spectroscopy

Abstract: The development of earth‐abundant catalysts for selective electrochemical CO2 conversion is a central challenge. CuSn bimetallic catalysts can yield selective CO2 reduction toward either CO or formate. This study presents oxide‐derived CuSn catalysts tunable for either product and seeks to understand the synergetic effects between Cu and Sn causing these selectivity trends. The materials undergo significant transformations under CO2 reduction conditions, and their dynamic bulk and surface structures are reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 66 publications
4
63
0
Order By: Relevance
“…This charge transfer from Sn/In into Cu led to partial positive charge on Sn/In atoms, indicated by the oxidized Sn and In species, and hence stabilizing the *COOH intermediate (CO-pathway). 17,24 Within the resolution of our XPS analysis we do not observe clear evidence of charge transfer, but rather both metals are f ully reduced on the surf ace. Thus, Cu-poor catalysts (HCOO-selective) is thought to enhance the HCOO-pathway by inhibiting the H-adsorption and stabilizing the *OCHO intermediate (HCOO-pathway), see in-situ SERS below.…”
Section: (Ii)mentioning
confidence: 53%
See 2 more Smart Citations
“…This charge transfer from Sn/In into Cu led to partial positive charge on Sn/In atoms, indicated by the oxidized Sn and In species, and hence stabilizing the *COOH intermediate (CO-pathway). 17,24 Within the resolution of our XPS analysis we do not observe clear evidence of charge transfer, but rather both metals are f ully reduced on the surf ace. Thus, Cu-poor catalysts (HCOO-selective) is thought to enhance the HCOO-pathway by inhibiting the H-adsorption and stabilizing the *OCHO intermediate (HCOO-pathway), see in-situ SERS below.…”
Section: (Ii)mentioning
confidence: 53%
“…Many other studies revealed a similar behavior f or Cu-Sn systems, where researchers reported Cu-Sn catalysts with high FE towards either CO or HCOO -. 9,17,22 For instance, Li et al 23 investigated CO2ER on Cu/SnO2 core-shell nanoparticles with various Sn shell thickness, finding the selectivity to strongly depend on said thickness, with thicker Sn shells showing Sn-like activity with high HCOOselectivity (FE ~90%), while thinner shell exhibited a high CO selectivity (FE ~93%). Moreover, our recently published work 17 reported a similar behavior f or Cu nanowires coated with ultrathin SnOx layers grown using atomic layer deposition, and detailed X-ray spectroscopic investigation revealed differing Sn speciation (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[89][90][91] This includes exciting opportunities in microscopies, such as transmission electron and atomic force microscopies (TEM and AFM, respectively), as well as spectroscopies, such as IR, Raman and X-ray absorption, photoelectron and emission spectroscopies (XAS, XPS and XES, respectively). [92][93][94][95][96] Experimentally, one challenge that lies ahead of performing these advanced operando studies, will be to establish whether the observed surface changes result from the catalytic reaction or the measurement itself. For example, it has recently been shown that a chemical segregation of Bi in BiVO 4 crystals takes place during TEM measurements forming Bi nanoparticles on the photoanode surface.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…3,9,11 Bimetallic catalysts offer possible synergetic effects among different metals to yield optimal binding of CO 2 and the key intermediate CO and have been demonstrated as a successful strategy for tuning selectivity in Cu-based catalysts. [18][19][20][21][22] Such an approach can be adapted for the modulation of CO binding on other early transition metals; for instance, the strong CO binding on Ni can be modulated by combination with a weak CO 2 /CO binding surface like In. 9,11 Nickel-indium composites were previously reported by He and coworkers 23 as a potential bimetallic composition with decreased CO binding energy capable of producing CO with appreciable selectivity.…”
Section: Introductionmentioning
confidence: 99%